Navigating Career Challenges in Gen Z: The Path from Parental Support to Career Adaptability through Future Work-Self - Pratiwi, Anggun; Salim, Rose Mini Agoes (LPPM Undiksha, 2025)
One of the external factors that contribute to increasing career adaptability is parental support. However, previous studies have shown mixed results regarding the relationship between parental support and career adaptability, indicating the existence of internal factors that can act as mediators, namely future work-self. Therefore, this study aims to examine the role of future work-self as a mediator in the relationship between parental support and career adaptability in Gen Z students. This study uses a quantitative approach with a mediation analysis design. The research sample consisted of 159 undergraduate and diploma students aged 19–25 years (M=21.2), who were selected using convenience sampling techniques. Data collection was carried out online using the Career Adaptability Scale-5 (CAS-5), Career-Related Parent Support Scale (CRPSS), and Future Work Self Scale (FWSS), which have been tested for validity and reliability. Data analysis was carried out using mediation analysis techniques with Jamovi software. The results showed that future work-self acts as a partial mediator in the relationship between parental support and career adaptability. Parental support has a significant direct effect on career adaptability as well as an indirect effect through the mediation of future work-self. This study confirms that parental support plays an important role in increasing the career adaptability of Gen Z students, both directly and through future work. The implication is that universities can develop career guidance programs that involve parents, while students need to build a clearer career vision.